Avaliação de qualidade de cursos superiores na modalidade a distância : um estudo na SEAD/UFES - Kolaga, Leonardo José Gomes (2014)
This research aimed to adjust an instrument for assessing quality have adapted to distance learning model proposed in the questionnaire High Performance Educational aiming to measure the quality of distance education courses at the Federal University of Espírito Santo. After adjustment, the questionnaire was applied in 2013 to 183 Students of distance learning courses for undergraduate in Accounting, Bachelor of Visual Arts and a degree in Physical Education offered by their departments through the Department of Distance Education. Data were analyzed using descriptive statistical analysis of frequency and contingency tables. The results show how the strengths Utility Course , Technical Capacity of Teachers and the Academic questions, and how the fledgling Internet Polo, Polo and Monitoring Library of Pedagogical questions, pointing out where to improve distance learning courses offered by UFES to improve their quality